Perú: elecciones 2021 en el contexto de la pandemia de COVID-19 - Acevedo Rojas, Elba Sissi (2021)
The holding of the parliamentary and presidential elections in Peru during the pandemic caused by COVID-19 was a controversial issue, to the point that its suspension or postponement was put into debate, especially if we take into account the effects that could have generated both in the right to vote as in the right to health. In this context, various constitutionalists, academics and international organizations pointed out that it was necessary to strengthen democratic institutions by exercising the citizen's right to vote, but it was necessary to have biosafety protocols to avoid further contagion. From an international perspective, there were successful cases in the implementation of the electoral process in 2020, South Korea being one of them as it used electronic voting, verifying, with subsequent tests, the low rate of contagion. The authors point out that this solution, in Peru, has been incorporated since 2010. However, it has not yet become widespread, which is why it could not be applied in the first and second electoral rounds in 2021. For this reason, in this article, the authors analyze the actions taken by the State in order to carry out the elections from the perspective of fundamental rights.